4 - The Emerging Architecture of a Regional Security Complex in the Lake Chad Basin - Tar, Usman A.; Mustapha, Mala (Africa Development, 2017)
This article explores the emerging regional security architecture to fight terrorism and insurgency in the Lake Chad Basin (LCB). It diagnoses the evolution of the Lake Chad Basin Commission (LCBC) as a sub-regional organization that unites Chad, Cameroon, Niger and Nigeria. In particular, the article critically investigates recent efforts by some members of the LCBC to create regional security architecture under the aegis of the Multinational Joint Task Force (MNJTF) to fight terrorism and insurgency within the Basin. The article argues that this new security mechanism in the Chad Basin is largely driven by resource geopolitics, regional security and Nigeria’s quest for hegemonic stability. It is argued that historical contradictions, linguistic differences, resource geopolitics, hegemonic politics, and local national politics have also hampered meaningful progress and undermined the basis for erecting robust new security architecture in Africa’s LCB.